Modeling of power generation with thermolytic reverse electrodialysis for low-grade waste heat recovery. (1st March 2017) - Kim, Deok Han; Park, Byung Ho; Kwon, Kilsung; Li, Longnan; Kim, Daejoong
Highlights: This work is the first attempt to develop an NH4 HCO3 -RED model for power generation. The activity and molar conductivity can be described with electrical conductivity. Actual permselectivity plays a critical role to estimate the RED performance. The model fits well to the experimental results with parametric variations. The optimal operating conditions can be achieved by the validated model. Abstract: Significant attention has been paid to closed-loop reverse electrodialysis (RED) systems using a thermolytic solution for low-grade waste heat energy recovery. They have several cost benefits when compared with open-loop RED with seawater and river water, such as no need of repetitive pretreatment and removal of locational constraints. This study presents the model of RED using ammonium bicarbonate (NH4 HCO3 ), one of the promising solutes for the closed-loop RED, whose ionization has not been clarified. Because of the unclarified electrochemical information of NH4 HCO3 electrolyte, the Planck-Henderson equation was used to approximate the membrane potential based on conductivity measurements, and the solution resistance was experimentally computed. Furthermore, the experimentally obtained permselectivity of the membrane was applied for a more precise estimate of the membrane potential. We found that the developed NH4 HCO3 -RED model was in good agreement with the experimental results under various operating conditions. We also characterized the net power density, which considers the pumping loss, by using our model. In our system, the maximum net power density of 0.84 W/m 2 was obtained with an intermembrane distance of 0.1 mm, a flow rate of 3 mL/min, and a concentration ratio of 200 (2 M/0.01 M) as optimum conditions. We expect that this study will improve our understanding of the NH4 HCO3 -RED system and contribute to relevant modeling studies, using NH4 HCO3 or some other compounds, for generating higher energy densities.